Carboxylic acid emissions from soybean biodiesel oxidation in the EN14112 (Rancimat) stability test. (1st June 2016) - de Carvalho, Anaildes L.; Cardoso, Erica A.; da Rocha, Gisele O.; Teixeira, Leonardo S.G.; Pepe, Iuri M.; Grosjean, Daniel M.
Highlights: Nine organic acids have been measured during soybean biodiesel oxidation. Formate contributed 82% of the total organic acid conductivity. The emission yield of formate was up to 3.8 × 10 −4  g per gram of biodiesel. Linoleate and linolenate methyl esters accounted for 90% of the biodiesel oxidation. Results are discussed with respect to engine corrosion and fugitive emissions. Abstract: Nine carboxylic acids (formic, acetic, propionic, butyric, succinic, oxalic, lactic, pyruvic and citric) and six inorganic ions (sodium, potassium, ammonium, chloride, nitrate and phosphate) have been measured by ion chromatography during soy biodiesel oxidation carried out according to the EN14112 oxidative stability test. Acid emission yields (gram of acid per gram of biodiesel) were small and ranged from 5.8 × 10 −6 for lactate to 3.8 × 10 −4 for formate. The corresponding molar yields calculated using MW = 291.9 for soy biodiesel ranged from 1.90 × 10 −5 for lactate to 2.46 × 10 −3 for formate. Emission yields were highest near the soy biodiesel oxidative stability index (OSI) of 5.43 ± 0.08 h ( n  = 3). Conductivity–time curves were well fitted by exponential equations, thus indicating first order behavior, and the oxidation rate constant was 0.655 ± 0.032 h −1 ( n  = 3). Conductivities calculated from the exponential curves agreed well, for samples collected near the OSI, with those calculated from measured ion concentrations and molar conductivities. For these samples formate contributed 52% of the total conductivity and for 82% of the conductivity of all measured organic acids. The FAME molecular composition of the soy biodiesel was measured before and after the EN14112 test and the biodiesel molecular weight (MW = 291.9) was calculated from the experimental data. Consistent with bond dissociation energies relevant to H atom abstraction from soy biodiesel C–H bonds, the two polyunsaturated FAME that bear bis-allylic H atoms, methyl linoleate (C18:2) and methyl linolenate (C18:3) together accounted for nearly all (92%) of the 36% biodiesel that had reacted during the test. The results are discussed for their relevance to diesel engine corrosion by carboxylic acids and with respect to possible emissions of carboxylic acids into the atmosphere.